Social Iconotext: the Stoics’ Club in John Galsworthy’s The Country House (1907) - Maxime Leroy (Cahiers Victoriens et Edouardiens)
The aim of this article is to describe Galsworthy’s use of visual writing and its relation to irony and social satire. It shows the importance of the club as habitus (Bourdieu), both real and metaphorical. In reference to Hamon’s concept of technème, it studies the importance and symbolic meanings of the club’s windows and doors. It presents the hypothesis that pictorial framing is a central trope put forward by the narrator as a key to reading the whole novel.